Physical Interaction of T Cells with Dendritic Cells Is Not Required for the Immunomodulatory Effects of the Edible Mushroom Agaricus subrufescens - Wilbers, Ruud H. P.; Westerhof, Lotte B.; van de Velde, Jan; Smant, Geert; van Raaij, Debbie R.; Sonnenberg, Anton S. M.; Bakker, Jaap; Schots, Arjen (Frontiers in Immunology, 2016)
Mushrooms are well known for their immunomodulating capacities. However, little is known about how mushroom-stimulated dendritic cells (DCs) affect T cells. Therefore we investigated the effect of mushroom compounds derived from seven edible mushroom species on DCs, their fate in DCs and the effect of the mushroom-stimulated DCs on T cells. Each mushroom species stimulated DCs in a different manner as was revealed from the DC’s cytokine response. Assessing DC maturation revealed that only one mushroom species, Agaricus subrufescens, induced complete DC maturation. The other six mushroom species upregulated MHC-II and CD86 expression, but did not significantly affect the expression of CD40 and CD11c. Nevertheless, mushroom compounds of all investigated mushroom species are endocytosed by DCs. Endocytosis is most likely mediated by C-type lectin receptors (CLRs) because CLR binding is Ca2+ dependent and EGTA reduces TNF-α secretion with more than 90%. Laminarin partly inhibited TNF-α secretion indicating that the CLR dectin-1, among other CLRs, is involved in binding mushroom compounds. Stimulated DCs were shown to stimulate T cells, however, physical contact of DCs and T cells is not required. Because CLRs seem to play a prominent role in DC stimulation, mushrooms may function as a carbohydrate containing adjuvant to be used in conjunction with anti-fungal vaccines.